1999
DOI: 10.1074/jbc.274.43.30349
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cytoplasmic-Retention Sequence in ERK2

Abstract: A key step in the signaling mechanism of the mitogenactivated protein kinase/extracellular signal-responsive kinase (ERK) cascade is its translocation into the nucleus where it regulates transcription and other nuclear processes. In an attempt to characterize the subcellular localization of ERK2, we fused it to the 3-end of the gene expressing green fluorescent protein (GFP), resulting in a GFP-ERK2 protein. The expression of this construct in CHO cells resulted in a nuclear localization of the GFP-ERK2 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
161
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 22 publications
16
161
1
1
Order By: Relevance
“…However, we were unable to find effects of phosphorylation on its uptake in permeabilized cells. This result is consistent with the observation that overexpressed ERK2 accumulates in the nucleus without being phosphorylated (42). Blockade of export, by favoring the dissociation of ERK2-MEK1 complexes, may be the primary event controlled by ERK2 phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…However, we were unable to find effects of phosphorylation on its uptake in permeabilized cells. This result is consistent with the observation that overexpressed ERK2 accumulates in the nucleus without being phosphorylated (42). Blockade of export, by favoring the dissociation of ERK2-MEK1 complexes, may be the primary event controlled by ERK2 phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…Most ERK-interacting proteins bind to ERK at one of its two well-characterized docking domains. The first is the ERK D recruitment site (DRS) (14)(15)(16)(17), which is used by proteins containing a D site (18)(19)(20). The D site consensus sequence is (R/K) 2-3 -X 1-8 -Φ-X-Φ, where X is any amino acid and Φ is a hydrophobic amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…For these experiments, we analyzed the distribution of the extracellular signaling-related kinase 2 (Erk 2) and the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunit GluR 2/3, normally enriched in the cytosol and membrane fractions, respectively (Bennett and Dingledine 1995;Rubinfeld et al 1999). Western blot analysis showed that the majority of Erk 2 immunoreactivity was contained in the cytosol fraction obtained from two weeks in culture hippocampal neurons.…”
Section: Aβ Caused Accumulation Of Amphiphysin At the Membrane Of Stimentioning
confidence: 99%